Pengaruh Komposisi Limbah Botol Plastik Sebagai Material Paving Block Bermutu Tinggi - WTP, James; Budiman (Indonesian Society of Applied Science, 2025)
Plastic waste is a type of waste that is difficult to decompose by natural processes so other alternatives are needed in its processing such as paving block construction materials. This study aims to determine the effect of the characteristics of plastic bottle waste and determine the compressive strength value of paving blocks. The method used in the study was an experiment in the Civil Engineering Laboratory, Politeknik Negeri Fakfak with a mixture composition of 100% PS, 50 PS: 50% KK, 40% PS: 60% KK with a rectangular paving block design type measuring 20 cm x 10 cm x 8 cm. The results showed that using 50% plastic bottle waste and 50% gravel affected the characteristics and compressive strength value of paving blocks. The compressive strength value of Paving Blocks using 50% PS bottle waste and 50% gravel was higher than the mixture of 100% PS bottle waste and the mixture of 40% PS bottle waste + 60% KK, which were 24.14 MPa, 22.79 MPa, and 21.58 MPa. The mix of 50% plastic bottle waste and 50% gravel showed good performance in the paving quality category, including a mixture of 20% PET and 80% fly ash with a quality of 24.20 MPa for use in pedestrian or parking areas.